The lion, the witch and the wardrobe ebook - Lewis, C. S. (The Chronicles of Narnia, 2009)
The Lion, the Witch and the Wardrobe is the second book in C. S. Lewis's The Chronicles of Narnia, a series that has become part of the canon of classic literature, drawing readers of all ages into a magical land with unforgettable characters for over fifty years. Four adventurers step through a wardrobe door and into the land of Narnia, a land enslaved by the power of the White Witch. But when almost all hope is lost, the return of the Great Lion, Aslan, signals a great change . . . and a great sacrifice. This ebook contains the complete text and art. Illustrations in this ebook appear in vibrant full color on a full-color ebook device and in rich black-and-white on all other devices. This is a stand-alone read, but if you would like to explore more of the Narnian realm, pick up The Horse and His Boy, the third book in The Chronicles of Narnia.